Quantification of cortisol and its metabolites in human urine by LC-MSn: applications in clinical diagnosis and anti-doping control - Arioli, Francesco; Gamberini, Maria Cristina; Pavlovic, Radmila; Di Cesare, Federica; Draghi, Susanna; Bussei, Giulia; Mungiguerra, Francesca; Casati, Alessio; Fidani, Marco (Analytical and bioanalytical chemistry, 2022)
The objective of the current research was to develop a liquid chromatography-MS n (LC-MS n ) methodology for the determination of free cortisol and its 15 endogenous metabolites (6β-hydroxycortisol, 20α-dihydrocortisol, 20α-dihydrocortisone, 20-β-dihydrocortisol, 20β-dihydrocortisone, prednisolone, cortisone, α-cortolone, β-cortolone, allotetrahydrocortisol, 5α-dihydrocortisol, tetrahydrocortisol, allotetrahydrocortisone, 5β-dihydrocortisol, tetrahydrocortisone) in human urine. Due to its optimal performance, a linear ion trap operating in ESI negative ion mode was chosen for the spectrometric analysis, performing MS 3 and MS 4 experiments. The method was validated for limit of detection (LOD) and limit of quantification (LOQ) (0.01 ng mL −1 and 0.05 ng mL −1 , for all compounds, respectively), intra- and inter-day precision (CV = 1.4–9.2% and CV = 3.6–10.4%, respectively), intra- and inter-day accuracy (95–110%), extraction recovery (65–95%), linearity (R2 > 0.995), and matrix effect that was absent for all molecules. Additionally, for each compound, the percentage of glucuronated conjugates was estimated. The method was successfully applied to the urine (2 mL) of 50 healthy subjects (25 males, 25 females). It was also successfully employed on urine samples of two patients with Cushing syndrome and one with Addison’s disease. This analytical approach could be more appropriate than commonly used determination of urinary free cortisol collected in 24-h urine. The possibility of considering the differences and relationship between cortisol and its metabolites allows analytical problems related to quantitative analysis of cortisol alone to be overcome. Furthermore, the developed method has been demonstrated as efficient for antidoping control regarding the potential abuse of corticosteroids, which could interfere with the cortisol metabolism, due to negative feedback on the hypothalamus-hypophysis-adrenal axis. Lastly, this method was found to be suitable for the follow-up of prednisolone that was particularly important considering its pseudo-endogenous origin and correlation with cortisol metabolism. Graphical abstract